Strategi Guru PAI dalam Membentuk Karakter Religius Siswa - Nur Afni Lubis; Murniyetti Murniyetti (An-Nuha, 2023)
PAI teachers have a role in shaping students' religious character, therefore PAI teachers' strategies in shaping students' religious character need to be considered. Because the strategy used will affect the formation of students' religious character. The purpose of this study was to determine the religious character of students at SMAN Binsus Dumai, to find out the strategies used by PAI teachers in shaping students' religious character, and to find out the factors that influence PAI teachers in shaping the religious character of students at SMAN Binsus Dumai. This research uses qualitative methods with a case study approach. The research was conducted at SMAN Binsus Dumai. The data collection techniques used are observation, interviews, and documents. The informants in this study were PAI teachers and students. The results of the study, first, the religious character of students in general can be said to be good because it has met the existing religious character indicators, character building strategies are carried out through integration through example, habituation, and advice. Third, Influencing factors are divided into internal and external factors.